1999
DOI: 10.1177/135245859900500211
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 19 locus apolipoprotein C-II association with multiple sclerosis

Abstract: We have used a PCR based method to analyze allelic frequencies in a (TG)n(AG)m microsatellite marker located in the first intron of the apolipoprotein C-II gene in French MS patients and controls. Samples were collected from 74 MS patients and from 102 controls. The distribution of microsatellite alleles differed between patients and controls (chi 2 = 7.82), showing a significant effect (P < 0.04) with MS due to the increased frequency of the allele 6 and a decrease frequency (P < 0.03) of allele I. Our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…At this point, we should mention that the high diversity of the compound STR (TG) n (AG) m rs139985133 is remarkable. Although it presented significant differences in allele frequencies, the range of repeats detected in Bolivians was quite similar to that found in our European population and in a French sample (Zouali et al, 1999). The sequencing of five individuals in this study confirmed a previous report that diversity at this locus is attributable to variation at both (TG) n and (AG) m motifs (Fornage et al, 1992).…”
Section: Discussionsupporting
confidence: 87%
“…At this point, we should mention that the high diversity of the compound STR (TG) n (AG) m rs139985133 is remarkable. Although it presented significant differences in allele frequencies, the range of repeats detected in Bolivians was quite similar to that found in our European population and in a French sample (Zouali et al, 1999). The sequencing of five individuals in this study confirmed a previous report that diversity at this locus is attributable to variation at both (TG) n and (AG) m motifs (Fornage et al, 1992).…”
Section: Discussionsupporting
confidence: 87%
“…Three other genomic screens (Ebers et al 1996;Sawcer et al 1996;Kuokkanen et al 1997) have shown some support for linkage to this region, and a meta-analysis of all four genomic screens (Wise et al 1999) identified 19q13 as the second-mostsignificant region after the MHC. Additional evidence for this region came from allelic association studies (Barcellos et al 1997;Zouali et al 1999;D'Alfonso et al 2000) and, more recently, from follow-up analyses by the Multiple Sclerosis Genetics Group (MSGG) in both North American (Pericak- and San Marinese populations (Haines et al 2000). As with most complex diseases, the data are not entirely consistent; not all studies have shown evidence of linkage (Chataway et al 1998;D'Alfonso et al 1999), and association results were based on polymorphisms in different markers.…”
Section: Introductionmentioning
confidence: 99%
“…10 It is coded for by a 3.7-kbp gene on chromosome 19, in close proximity to the Apo-CII locus, which has been implicated in MS susceptibility in one study. 11 Apo-E is found in chylomicra and VLDL and also in the HDLc, HDL 2 , and b-VLDL lipoprotein remnant complexes. It exhibits specificity for the Apo-B/E receptor, which is expressed in liver, macrophage, astrocyte and oligodendrocyte cells, amongst others.…”
Section: Introductionmentioning
confidence: 99%